2013
DOI: 10.2196/jmir.2640
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Internet-Based Self-Management Support in Adults With Asthma: Randomized Controlled Trial

Abstract: BackgroundLong-term asthma management falls short of the goals set by international guidelines. The Internet is proposed as an attractive medium to support guided self-management in asthma. Recently, in a multicenter, pragmatic randomized controlled parallel trial with a follow-up period of 1 year, patients were allocated Internet-based self-management (IBSM) support (Internet group [IG]) or usual care (UC) alone. IBSM support was automatically terminated after 12 months of follow-up. In this study, IBSM suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 29 publications
0
81
0
Order By: Relevance
“…Web-based systems offer less burdensome self-management support, which may improve asthma outcomes [13]. Nowadays, smartphones have become an integral part of life and mobile healthcare (mHealth) systems are promising tools that may revolutionise asthma selfmanagement.…”
Section: Introductionmentioning
confidence: 99%
“…Web-based systems offer less burdensome self-management support, which may improve asthma outcomes [13]. Nowadays, smartphones have become an integral part of life and mobile healthcare (mHealth) systems are promising tools that may revolutionise asthma selfmanagement.…”
Section: Introductionmentioning
confidence: 99%
“…We have no evidence of studies with difficult to control asthmatic patients as the next therapeutic step is to introduce monitoring through an e-health system [29][30][31][32][33]. Short term outcomes in our study show a decrease of patients attending emergency room for asthma exacerbations, as well as improved adherence and treatment compliance which is leading to favourable clinical consequences trough improving respiratory function.…”
Section: Conclusion and Discussionmentioning
confidence: 70%
“…In the study by Van der Meer et al [29] with patients with mild to moderate persistent asthma, it was demonstrated that an internet-based self-management (IBSM) support program during 1 year leads to improved asthma-related quality of life, asthma control, lung function, and the number of symptom-free days as compared to usual care (UC) alone. A post hoc analysis of this study [30] showed that patients with asthma that were not well controlled benefited the most from IBSM support. In addition, this study showed that at 12 months of follow-up, about 60% of the patients were still using the program of their own initiative.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations